Characterization of Band-E Narges magnetite iron ore for mineral processing (2018)
The Band-e Narges deposit is located about 70 km northeast of the city of Badrud, northern Isfahan province. Band-E Narges ore deposit is mining for magnetite. To release valuable minerals, crushing and grinding implemented for separation ore from the gangue. Magnetic separation and flotation methods for upgrading magnetite iron ore were carried out in different experimental conditions with varied parameters. The particle size of the initial content was 74 microns for flotation, and 150 microns for magnetic separation. The initial samples, with the iron grade of 43.4% and sulfur of 1.9%, are individually subjected to upgrading by floatation and magnetic separation during which the affecting parameters for each method were optimized. The improvement in the optimal condition for magnetic separation culminated in 60.85% for the iron grade, 85.21% iron for recovery and 1.08% for sulfur content. The upgrading by floatation in the optimal mode produced 60.02% iron grade, 80.41% iron recovery and 0.95% sulfur content. To determine the best method for the pre-concentration stage of ore, the content gained from each technique passed reclining for grad improvement. The final content obtained from the magnetic separation of was undergone the floatation test yielded to a content with 64.3% iron grade, 77.15% iron recovery and 0.7% sulfur content. The use of magnetic separation as a pre-concentration stage for floatation method is proposed as an economical method for improving the grade of the iron and reduce the sulfur content and to avoid the high cost of grinding, which is costly part of processing procedures.